Peningkatan Minat Belajar Peserta Didik Kelas XII Pada Materi Kombinatorika Melalui Aplikasi Quizizz Dengan Pendekatan Culturally Relevant Teaching: Increasing the Learning Interest of Grade XII Students in Combinatorial Materials through the Quizizz Application with a Culturally Relevant Teaching Approach - Ifa Umiah; Hasrul (Jurnal Education, 2025)
This study is designed to investigate the enhancement of learning interest among twelfth-grade students in the subject of Combinatorics through the Quizizz application using the Culturally Relevant Teaching (CRT) approach. The type of research conducted is Classroom Action Research (CAR), carried out in two cycles. The subjects of the study consist of 36 twelfth-grade students at SMA Negeri 21 Makassar. Data were collected using descriptive methods. The results indicate a significant increase in students' learning interest after the implementation of the Quizizz application integrated with the CRT approach. The findings show a notable improvement in the average comprehension score of students, from 64.44 in the pre-cycle to 87.22 in the second cycle. Furthermore, the mastery level of students increased from 30.56% in the first cycle to 83.33% in the second cycle. These findings suggest that the integration of the Quizizz application in learning can enhance motivation and understanding of material often considered abstract. This research also emphasizes the importance of utilizing technology in education that supports the principles of Learning 4.0, as well as the need for appropriate pedagogical approaches to optimize the learning experience